IDENTITY OF THE FEMININE CREOLE IN JEAN RHYS’S NOVEL-WIDE SARGASSO SEA - Dr. Shaymaa Neamah Almkhelif (American Journals Publishing, 2024)
The current article briefly discusses the identity of the feminine Creole in Jean Rhys’s novel Wide Sargasso Sea. The article begins with a brief introduction that presents the novel as a prequel to Charlotte Bronte’s novel Jane Eyre. The focus is on the voice of women who suffers patriarchy by such colonialist husbands as Rochester. The article then analyzes the identity of Antionette as a creole woman. Her husband’s consistent attempts at changing her identity from a Creole into an English woman ultimately lead her to madness and then death. Finally, the article ends with the conclusion which sums up the fact that the voice of the creole Antionette overcomes both madness and death.
Keywords: Feminine, identity, Creole, patriarchy, colonialism.